The Effect of Chronic Exercise on Energy and Fatigue States: A Systematic Review and Meta-Analysis of Randomized Trials - Wender, Carly L. A.; Manninen, Mika; O’Connor, Patrick J. (Frontiers in Psychology, 2022)
In this meta-analysis, we synthesized the results of randomized controlled trials of different exercise training interventions on participants’ feelings of fatigue, energy, and vitality. The search of studies was conducted using six databases as well as several other supplementary search strategies available before December 2021. The initial search generated over 3,600 articles with 81 studies (7,050 participants) and 172 effects meeting the inclusion criteria. We analysed the effects from the studies using a meta-analytic multivariate model and considered the potential moderating effect of multiple variables. Our analysis revealed exercise to decrease the feelings of fatigue by a small effect size (g = -0.374; CI 95% [-0.521, -0.227]), increase energy by a small-to-moderate effect size (g = 0.415; CI 95% [0.252, 0.422]), and to increase the feeling of vitality by a moderate effect size (g = 0.537; CI 95% [0.404, 0.671]). All main results remained robust after several sensitivity analyses using different statistical estimators, and consideration of outlier and influential studies. Moreover, moderator analyses revealed significant effects of exercise intensity, and intervention duration on fatigue, exercise intensity and modality on energy, and participant health, exercise intensity, modality, and exercise training location on vitality. We conclude that when groups adopt a moderate intensity exercise training program while participating in a randomized trial, compared to controls, this typically results in small-to-moderate average improvements in feelings of fatigue, energy and vitality.